HISTORICAL ASPECTS OF DEVELOPMENT OF THE MANAGEMENT SYSTEM OF THE PRODUCTIVE INFRASTRUCTURE - Gasanov, M A (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the historical aspects of the development of the production infrastructure components. Basing on the study and analysis of historical documents, the author considers the most important periods of formation and development of production infrastructure and presents the main stages of historical formation of its types. It is noted that the modern stage of historical development is characterized by the growing role and importance of production infrastructure, which increasingly determines the state of the economy of the country and its regions.